2000
DOI: 10.1180/000985500546729
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical modelling of diagenetic reactions in a sub-arkosic sandstone

Abstract: A reaction path model was constructed in a bid to simulate diagenesis in the Magnus Sandstone, an Upper Jurassic turbidite reservoir in the Northern North Sea, UKCS. The model, involving a flux of source rock-derived CO2 into an arkosic sandstone, successfully reproduced simultaneous dissolution of detrital K-feldspar and growth of authigenic quartz, ankerite and illite. Generation of CO2 occurred before and during the main phase of oil generation linking source rock maturation with patterns of diagenesis in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…As discussed above, interaction between CO 2 -rich rich hydrothermal fluids and siliciclastic rocks will enhance the cation release leading to formation of a widespread clay, carbonate and quartz mineral association (Huang and Longo, 1994;Barclay and Worden, 2000;Kaszuba et al, Battaglia et al, 2007). Assuming the illitic clays and carbonates were formed in a similar temperature range from roughly 80°C (smectite-rich) to 170°C (illite-rich) and from fluids with a similar origin we can estimate the oxygen isotope composition of fluids from which the carbonates precipitated (Table 2).…”
Section: Stable Isotope Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, interaction between CO 2 -rich rich hydrothermal fluids and siliciclastic rocks will enhance the cation release leading to formation of a widespread clay, carbonate and quartz mineral association (Huang and Longo, 1994;Barclay and Worden, 2000;Kaszuba et al, Battaglia et al, 2007). Assuming the illitic clays and carbonates were formed in a similar temperature range from roughly 80°C (smectite-rich) to 170°C (illite-rich) and from fluids with a similar origin we can estimate the oxygen isotope composition of fluids from which the carbonates precipitated (Table 2).…”
Section: Stable Isotope Resultsmentioning
confidence: 99%
“…At the earliest stage of the reaction, kaolinite will precipitate from HCO 3 À1 -rich acidic fluids. As the reaction proceeds, depending on the availability of cations (particularly K + ), precipitation of illite-smectite will follow in a slightly acidic to neutral environment (e.g., Barclay and Worden, 2000;Battaglia et al, 2007). The remaining, more cation-rich fluids will lead to deposition of carbonate minerals and silica (e.g., Barclay and Worden, 2000;Kaszuba et al, 2006) (see below).…”
Section: Clay Mineralogymentioning
confidence: 98%
“…Liewig and Clauer 2000;Wilkinson and Haszeldine 2002). Meshwork illite precipitation is most likely related to increasingly acidic/CO 2 -rich pore waters during early stages of oil charging (Cookenboo and Bustin 1999;Barclay and Worden 2000).…”
Section: Mesodiagenesismentioning
confidence: 98%
“…However, the amount of pressure dissolution of quartz is difficult to quantify. Furthermore, the K‐feldspar dissolution can generate excess SiO 2 (Barclay & Worden, ; Thyne et al, ), which may also be a likely source for quartz cement as shown in Figure . Moreover, as Figure a shows, there is external silica source for precipitation of quartz cement, the catagenesis of adjacent shales may be a probable source (Foscolos & Powell, ).…”
Section: Discussionmentioning
confidence: 99%